Pengaruh Frekuensi Irigasi terhadap Pertumbuhan dan Hasil Padi (Oryza sativa L.) - Chairil Ezward; Siska Efendi; Jauharil Makmun (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2018)
The fluctuations of the availability of water is a matter of in growth this licensing process for rice. The availability of the water sufficient is advantages for the growth of plants rice farming. The rice crop need the different volume for each phase the real sector growth reached. Water had a very important role at the time of the nymph formation and initiation panicles . This studied attempts to watchful over the influence of the waterworks frequency on the growth and production of rice fields with water. Design was used in this research was Random design a group ( a shelf ) non factorials consisting of 5 treatment and 3 preparation of test questions, Namely A = ( times inundated by persistently even rising up early ), B = the frequency of of waterworks 4 once over days, C = the frequency of of waterworks 8 once over days, D = 12 day once upon the irrigation system, and E = frequency irrigation 16 days once. Data was analyzed statistically each observation treatment, and when markedly dissimilar was continued by test said different real give an bnj ) the first 5 percent. Based on the research, with analysis design a rack non factorials, can be concluded that the use of frequency irrigation to optimize its growth and the production of in plants rice yield real impact to higher plants and heavy grain dry. Treatment best conditions exist on treatment b ( the frequency of of waterworks 4 once over days ) with high in plant 141 , 33 and weighed of dried grain pt pgn promised to supply 37,78 the most ten grams of / a clump of.